The Relationship Between Knowledge and Economy With Client Interest In Performing Root Canal Treatment At One Icon Dental Clinic Gresik - Rizky, Wildatus Sholikhah Novita; Zuhroh, Diah Fauzia; ‎, Widiharti (INNOVATION RESEARCH JOURNAL, 2025)
Dental and oral health will be disturbed if hygiene is not maintained and will cause dental caries. If caries is left untreated, the bacteria will spread to the point of touching the nerves. The management is by performing root canal treatment. To Analyze the relationship between the client's knowledge and the client's economic status with the client's interest in performing root canal treatment at One Icon Dental Clinic Gresik. This type of research is an analytical survey using a survey research method with a cross sectional research design. The data collected are the level of client knowledge and the client's economic status as well as the client's interest in root canal treatment at OIDC Gresik in November 2024. The sample in this study is 108 respondents and uses a non- probability sampling data collection technique by means of purposive sampling with a data analysis technique using Spearman Rank. Most clients (58.3%) have a moderate level of knowledge. Most of the clients (74.1%) are high-income. Almost half of clients (47%) fall into the interest category. The relationship between the level of knowledge and the client's interest is that it has a significant relationship with p 0.000 (≤0.05) and has a moderate relationship and the direction of the correlation is positive (unidirectional). The relationship between economic status and client interest is that it has a significant relationship with p 0.000 (≤0.05) and has a very strong relationship and the correlation direction is positive (unidirectional). There is a relationship between the level of knowledge and economic status of the client and the client's interest in root canal treatment at One Icon Dental Clinic Gresik.